Substrate cycles and drug resistance to 1-beta-D-arabinofuranosylcytosine (araC) - Fernandez Calotti, Paula (2005)
Acute myelogenous leukemia (AML) is the most common form of acute leukemia in adults. After diagnosis, patients with AML are mainly treated with standard induction chemotherapy combining cytarabine (araC) and anthracyclines. The majority of them achieve complete remission (CR) (65-80%). However, prospects for long-term survival are poor for the majority of patients. Resistance to chemotherapy therefore remains a major obstacle in the effective treatment of patients with AML. In this review, we highlight the current knowledge of substrate cycles involved in normal deoxynucleoside triphosphate (dNTPs) metabolism and their possible role in drug resistance to araC. © 2005 Taylor & Francis Group Ltd.